2016
DOI: 10.1007/s40890-016-0028-3
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Speed Characteristics and Alignment Design Consistency for Mountainous Roads

Abstract: Vehicle drivers continuously make decisions and execute them while driving on a roadway. It requires perception, comprehension and prediction of roadway conditions. Studies show that the decision-making process and driver performance greatly depends on situational awareness. Drivers intend to operate vehicles at safe speed based on the roadway geometric features. These features are characterized by gradient, horizontal curvature, length of curves and tangent sections, superelevation, etc. Perceptive and consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 13 publications
(23 reference statements)
1
18
0
Order By: Relevance
“…However, vehicle fitted with GPS devices can make driver over sensitive about vehicle speed (Nama et al 2016). Data collection using roadside laser detectors and sensors cannot identify vehicle categories accurately.…”
Section: Study Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, vehicle fitted with GPS devices can make driver over sensitive about vehicle speed (Nama et al 2016). Data collection using roadside laser detectors and sensors cannot identify vehicle categories accurately.…”
Section: Study Objectivesmentioning
confidence: 99%
“…Table 1 represents the summary of a few relevant models. Gong and Stamatiadis (2008) (Nama et al 2016). However, availability of speed prediction model for four-lane divided horizontal curves is very limited, especially in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of horizontal and vertical alignment on their traffic operation was studied on 19 uniform segments from Spain; it was proved that deviations on horizontal alignment or longitudinal profile may produce bad estimation if they are not considered on the analysis procedure [7]. The 85th percentile vehicle speed had been adopted as part of geometric design consistency evaluation criteria [8].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that curve radii of 400 m and higher have an insignificant effect and radii above 800 m have no effect on vehicle operating speed [3,4]. Furthermore, the effect of a horizontal curve on vehicle operating speed is significant in flatter gradient [5]. Horizontal curve radius is the most common independent parameter in the operating speed prediction models at MC [3,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies are based on traffic with stronger lane discipline. Nama et al [5] extensively studied the speed characteristics of passenger car and heavy commercial vehicle with weak lane discipline but did not provide a speed prediction model. On the other hand, Sil et al [15] developed the speed prediction model for passenger cars at MC only.…”
Section: Introductionmentioning
confidence: 99%